Competences for Providing Oral Health Care to Care-Dependent Older Adults—Defining Learning Objectives for the German Undergraduate Dental Curriculum Through a Delphi Study - Hillebrecht, Anna Lena; Barbe, Anna Greta; Krämer, Susanne; Auerbacher, Marc; Semper-Hogg, Wiebke; Spies, Benedikt C.; Linde, Philipp; Erfurt-Berge, Cornelia; Kossioni, Anastassia; Farin-Glattacker, Erik; Bitter, Kerstin (European Journal of Dental Education, 2026)
Background/Aim: One of the largest unmet dental care needs in Germany concerns dependent older people (DOP). The aim of this Delphi study was to define learning objectives (LOs) for the dental curriculum, specifying the skills, abilities, and attitudes necessary to enable and motivate future dentists to provide oral health care to DOP. Method: LOs from international guidelines for special care dentistry and gerodontology were mapped and aligned with the current guidelines of the German dental curriculum. Based on this alignment, comprehensive LOs were formulated and ranked through a Delphi process. The target group consisted of dental education experts from German universities (14 in first round/12 in second round), all of whom had expertise in gerodontology or special care dentistry. Results: A framework consisting of six competence areas was established: (1) Care dependency in older individuals, (2) Access & barriers to oral health, (3) Legal aspects, (4) Communication, (5) Effects of medical and functional condition on oral health, (6) Clinical management of DOP. The participants agreed on a total of 43 LOs. After refinement, a graduate profile for dental students in Germany with 21 LOs with a focus on the oral health of DOP was developed. Discussion: The results of this study can be used to provide standardised education about dental care of DOP in Germany. By implementing the LOs and the graduate profile to the undergraduate dental curriculum, students should be prepared for the requirements of dental care for DOP after graduation.
CRIS-Team Scopus Importer:2026-01-30
Keywords: Delphi study; dependent older people; gerodontology; graduate profile; learning objectives; oral health care